The impact of food availability on food security in developing countries - Abdul Manap, Nur Marina; Ismail, Normaz Wana (Penerbit Universiti Malaysia Terengganu, 2016)
World has seen continued famine, starvation and malnutrition, mostly concentrated within the poor and developing third-world countries. Starvation and malnutrition have a negative impact on health, leading to poor productivity and thus gradually affecting overall economic growth. Factors such as climate change, natural disasters, overpopulation, food crisis, higher food prices and diminishing resources have worsened the situation and are now beginning to impact the rich and developed countries. These problems have become global concerns and are recognized worldwide as food security issues. Global food shortages, if unchecked could lead a major crisis and present major challenges to humanity’s food security. Food security was defined in the World Food Summit (1974) as the availability at all times of adequate world food supplies of basic foodstuffs, to sustain a steady expansion of food consumption and to offset fluctuations in production and prices. Increase in population will have the same effect on the consumption of food per capita and will increase the changes in diets toward high-nutrition foods due to increase in income for certain countries. In order to overcome this situation, developing countries need to focus on their food availability problems in order to ensure sufficiency and affordability. Food availability is derived from food production, food imports and food aid.